2020
DOI: 10.1111/raq.12520
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental carbon sources applied in biofloc technology aquaculture systems: types, effects and future research

Abstract: Biofloc technology (BFT) systems have been driven towards increased sustainability in the last decade. BFT depends on maintenance of the optimal carbon-to-nitrogen (C/N) ratio through supplementation with organic carbon sources. The types of carbon sources and addition strategies are critical considerations in BFT systems. Thus for the purpose of this review, a thorough search of the literature was conducted to gather relevant information from reliable sources, ranging from reputable journals to books and usef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 135 publications
0
23
0
Order By: Relevance
“…After adaptation to experimental conditions for two days, these tanks were randomly divided into three groups (six replicates per group): control group, feeding basal diet (C/N ratio of ~6:1, 44.20%, w/w, carbon and 7.04%, w/w, nitrogen; AlphaFeedCo., Ltd., Shenzhen, China); CN10 group, feeding the mixture of basal diet and sucrose (42.1%, w/w, carbon, purity 99%) with a ratio of 5:3 to obtain a C/N ratio of ~10:1; CN15 group, feeding the mixture of basal diet and sucrose with a ratio of 2:3 to obtain a C/N ratio of ~15:1. Previous studies indicated that a C/N ratio in the substrate ranging from 10 to 20 is considered optimal for heterotrophic bacteria to assimilate NH 4 -N 48 50 . When the C/N ratio is between 8 and 10, it depends on the joint action of autotrophic microorganisms and heterotrophic microorganisms to remove inorganic nitrogen; but when the C/N ratio reaches 15, inorganic nitrogen can basically be consumed by the assimilation of heterotrophic microorganisms 51 , 52 .…”
Section: Methodsmentioning
confidence: 99%
“…After adaptation to experimental conditions for two days, these tanks were randomly divided into three groups (six replicates per group): control group, feeding basal diet (C/N ratio of ~6:1, 44.20%, w/w, carbon and 7.04%, w/w, nitrogen; AlphaFeedCo., Ltd., Shenzhen, China); CN10 group, feeding the mixture of basal diet and sucrose (42.1%, w/w, carbon, purity 99%) with a ratio of 5:3 to obtain a C/N ratio of ~10:1; CN15 group, feeding the mixture of basal diet and sucrose with a ratio of 2:3 to obtain a C/N ratio of ~15:1. Previous studies indicated that a C/N ratio in the substrate ranging from 10 to 20 is considered optimal for heterotrophic bacteria to assimilate NH 4 -N 48 50 . When the C/N ratio is between 8 and 10, it depends on the joint action of autotrophic microorganisms and heterotrophic microorganisms to remove inorganic nitrogen; but when the C/N ratio reaches 15, inorganic nitrogen can basically be consumed by the assimilation of heterotrophic microorganisms 51 , 52 .…”
Section: Methodsmentioning
confidence: 99%
“…It is suggested that the type of carbon source, for example glucose, starch, glycerol, logan powder, polybutylene succinate (PBS), PHB, brown sugar or molasses (Table 5), used in BFT systems can influence the nutritional content of the bioflocs. When applied in BFT systems for the formation of bioflocs, these carbon sources are categorised into various types according to their chemical composition and the speed with which they release DOC into the system 261 28 affirmed that adding carbohydrates to BFT systems results in the proliferation and dominance of heterotrophic bacteria and reduces the total Vibrio count in the water.…”
Section: Management Of Bacterial Communities In Bft Aquaculture Systemsmentioning
confidence: 99%
“…When applied in BFT systems for the formation of bioflocs, these carbon sources are categorised into various types according to their chemical composition and the speed with which they release DOC into the system. 261 Panigrahi et al 28 affirmed that adding carbohydrates to BFT systems results in the proliferation and dominance of heterotrophic bacteria and reduces the total Vibrio count in the water.…”
Section: Carbohydrate Types and Supply Strategiesmentioning
confidence: 99%
“…After the establishment of a biofloc-based system, there is no need to add organic carbon into culture water for the growth of heterotrophic bacteria and the development of biofloc. This is different from the traditional proposition, which highlights the increase in input C/N ratio through organic carbon addition to accelerate the assimilation of NH 4 + -N by heterotrophic bacteria and convert it to bacterial protein without producing NO 2 − -N and nitrate nitrogen (NO 3 − -N) [ 16 , 17 , 18 ]. However, continuous addition of organic carbon can generate large amounts of heterotrophic biofloc biomass in the culture system, which increases not only the input cost but also the management difficulties in terms of solids removal and oxygen supplement [ 5 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, increasing the C/N ratio can induce a shift of the bacterial community of biofloc [ 10 , 15 , 19 ], which could have very significant impacts on water quality control and shrimp production performance [ 15 , 21 ]. It is thought that the input C/N ratio is one of the critical factors affecting growth rate of different microbial communities, thereby generating different nitrogen conversion pathways and microbial biomass yields [ 15 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%